Dinosaur Demise and Species Extinction Generally: Role of Whole-Earth Decompression Dynamics - Herndon, J. Marvin (European Journal of Applied Sciences, 2025)
Since 1979, fundamental scientific contradictions are systematically ignored and the scientific community continues to assume without legitimate basis that previous, underlying ideas are correct even though refuted and shown to be no longer viable. Consequently, for decades, members of the geoscience community have attempted unsuccessfully to reconcile major species extinctions with geophysical phenomena based upon false assumptions. I describe briefly the false assumptions that have impeded understanding, and demonstrate how logical, causal relationships related to species extinction follow from my new geoscience paradigm called Whole-Earth Decompression Dynamics. The mechanism for triggering whole-Earth decompression episodes, related to geomagnetic changes, is as a multi-stage amplifier that involves disruption of georeactor sub-shell convection either by trauma or by a change in solar flux impinging on Earth’s magnetic field. Disruption of sub-shell convection results in extra uranium settling-out, which causes a burst of nuclear fission energy, which replaces some of the lost heat of protoplanetary compression, which causes a burst in whole-Earth decompression, which results in a burst of heat emplacement at the base of the crust and/or Earth’s surface experiencing decompression-driven movement, the extent of which is a function of the degree of sub-shell convection disruption. The geomagnetic mechanism for triggering whole-Earth decompression episodes of major-scale provides a logical, causally-related explanation of species extinction connected to magnetic reversals and excursions that involves splitting the continental crust, opening new ocean basins, lowering sea-levels, toxifying oceans, as well as major volcanic eruptions, earthquakes and environment devastation.